Mononormativity Sentiment Towards Polygamous Ustadz on Social Media - Muhammad Noval Abdul Rozak; Sri Kusumo Habsari; Eva Farhah (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Mononormativity widely embraced by societies, often leads to negative sentiment toward non-monogamous relationships. Polygamy, as a form of non-monogamy, challenges this norm, particularly when practiced consensually, revealing a divergence from assumptions that label such relationships as destructive. In Indonesia, where Islam predominates, polygamy is conditionally legitimate under religious law and mutual agreement. However, it frequently faces public criticism and rejection, especially on social media. Religious figures like Ustadz Hanan Attaki, who practice polygamy, often become targets of this negative sentiment, revealing the tension between cultural norms, religious legitimacy, and societal perceptions. This study aims to analyze how mononormativity functions as a form of knowledge-power in constructing negative sentiments towards polygamists, especially ustadz, on social media. Utilizing primary data from social media comments and secondary data from online media and supporting articles, the research employs an explanatory sequential mixed method, where quantitative data supports qualitative insights. Combining sentiment analysis using NVivo and Foucaldian discourse analysis, the paper uncovers how societal norms and power structures shape and reinforce negative sentiments towards polygamists. The quantitative data provides a broad understanding of public opinion, while the qualitative analysis delves deeper into the discourses that perpetuate mononormativity. Through this integration, the study highlights the significant influence of mononormative discourse in shaping societal attitudes and maintaining power dynamics that marginalize non-monogamous relationships.